Ingresso no curso de educação especial: aspectos motivadores ao processo de escolha profissional - Machado, Jones Carlos Plate (2021)
This dissertation, part of the Master’s Course in Education, in the Education, Inclusion and Difference research line, of the Graduate Program in Education at the Universidade Federal de Santa Maria (UFSM) had as its general objective to know the aspects that motivate professional choice of academics fron the Special Education Teacher Training Course at a Public University of Rio Grande do Sul, who agreed to participate in the study. Data collection was performed by filling out a questionnaire using Google Forms, with qualitative analyses. It was possible to observe that diferente factors may be related to professional choice, from personal interests, proximity to people who have some type of disability, whether they are close or colleagues who have been through the Family, school or social circle. Another aspect related to the search for the course is the need to feel able to act in front of students with disabilities or some other specificity or characteristic that may interfere with learning. It is concluded that the processo of choosing a fivem professional training is variable, the factors that motivate this process are intervening, but the experiential contexto and the subject’s personality are highlighted.